Sociodemographic characteristics of food festival attendees and their relationship with motivations - Carvache-Franco, Mauricio (2025)
Conducting research on food festivals is vital for advancing the development of tourist destinations. This study, conducted at the Bahrain Food Festival on the eastern coast of the Persian Gulf, aimed to achieve the following objectives: (1) To identify the motivational factors that drive visitors to food festivals and (2) to determine the relationship between these attendees’ sociodemographic characteristics and motivations. Motivations are often categorized as push factors (internal desires) and pull factors (external incentives). Three hundred eighty valid questionnaires were collected online from event attendees, and statistical techniques such as factor analysis and multiple regression were applied. The findings revealed five motivational dimensions associated with food festivals: Local cuisine, Art, Entertainment, Socialization, and Escape and Novelty. Moreover, some sociodemographic characteristics were found to be predictors of motivations. Specifically, attendees with higher levels of education exhibited greater motivation for Local Food and Art. Additionally, scientific researchers and business people were highly motivated by the Art dimension alone. Furthermore, younger attendees were found to be more motivated by Entertainment, while those attending with friends or colleagues were more inclined toward Socialization. These findings offer valuable insights into the management of food festivals and contribute to the existing academic literature in this field.